Does stapled colorectal anastomosis in anterior resection always guarantee restoration of intestinal continuity? - P. V. Tsarkov; A. Yu. Kravchenko; I. A. Tulina; P. B. Tsugulya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To analyze causes and frequency of non-closure of colonic stomas created for prophylactic or medical reasons after anterior resections with stapled colorectal anastomosis for cancer of the rectum.Material and methods. Results of treatment of 215 patients after anterior rectal resection with formation of stapled colorectal anastomosis from June, 2006 to June, 2011 were analyzed.Results. Creation of colorectal anastomoses after anterior and low anterior resections is quite often accompanied by formation of «temporary» protective stoma to reduce consequences of possible anastomotic leak (AL). Nevertheless, in some patients these «temporary» stomas are never reversed.. By the moment of discharge from hospital 111 (52%) patients had colostomies: in 103 of them were preventive double-barrelled transverse colostomies were created at primary surgical intervention, the remaining 8 patients underwent colostomy formation in postoperative period because of development of AL. Average follow-up was 32,3 months (12 to 70 months). Among 111 patients the restorative operations were done in 96 (86,5 %). At multivariant analysis the following factors were identified as predictors of non-closure of stoma after anterior resection: death due to disease progression (correlation coefficien = 0,24) and chemotherapy treatment (correlation coefficient = 0,22).Conclusions. The risk of «temporary» stoma nonclosure even in specialized center is 13,5%. When sphincter-sparing operations are performed for all stages of rectal cancer the most essential risk factors of non-closure of stoma were progression of disease and chemotherapy treatment and patient death related to it, and patient’s death.